An AIE-active probe acts as novel tool for rapid and accurate quantitative antifungal susceptibility assessment - Zheng, Fen; Ge, Xiaoxue; Guan, Yajuan; Zhou, Qixian; Shi, Renren; Zhao, Jiayi; Situ, Bo; Zhang, Jing; Rui, Yongyu (Frontiers in Microbiology, 2025)
ObjectivesCommon antifungal susceptibility testing methods are often time-consuming and subject to interpretation bias in endpoint determination, making them inadequate for clinical applications. We aim to develop a rapid and accurate quantitative method for routine antifungal susceptibility testing in diagnostic laboratories by employing the aggregation-induced emission (AIE) luminogen TBP-2.MethodsThe AIE luminogen TBP-2 with two positive charges was introduced to develop an antifungal susceptibility testing protocol based on the reference broth microdilution (BMD) method. The minimum inhibitory concentration of different drugs against Candida was determined by detecting changes in fluorescence intensity. A total of 76 clinical isolates of Candida albicans (C. albicans) were collected to evaluate the performance of the platform. The results obtained by the TBP-2-based method were compared with those obtained by the reference BMD.ResultsThe TBP-2-based method enables endpoint determination by detecting fluorescence intensity after a co-incubation period of 8 h with C. albicans in drugs. The excellent essential agreement between the TBP-2-based test and BMD among 76 clinical isolates was observed for all the four drugs. The categorical agreement between two methods was 100% for amphotericin B and 5-flucytosine, 96.1% for fluconazole and 97.4% for voriconazole. Only minor errors were found in fluconazole and voriconazole, at 3.9 and 2.6%, respectively, with no errors found in very major errors and major errors.ConclusionThe TBP-2-based method provides rapid and accurate quantifiable endpoints, aiding in the timely selection of appropriate antifungal therapy, and offering opportunities for automation and widespread application.